Comparative study on national HPC core strategies for AI adaptation-focusing on South Korea and the United States - Shim, Hyungwook; Suh, Minho (Edelweiss Applied Science and Technology, 2025)
This study compares high-performance computing policies in the United States and South Korea to derive an effective future policy model, an efficient governance structure, and key policy implications. By analyzing the National Strategic Computing Initiative and the 3rd National HPC Master Plan, the study examines their technology development and industrial promotion strategies based on five key criteria: policy priorities, implementation system, technology development strategy, infrastructure, and resource management. The findings reveal that the NSCI prioritizes global technological leadership, next-generation technology development, and cybersecurity, whereas the Master Plan focuses on AI-driven demand, technological independence, and industrial applications. These differences highlight the need for a concrete policy model with execution roadmaps, particularly for quantum computing resource development and core software technologies tailored to new architectures. Strengthening governance structures and enhancing resource management strategies will be crucial for ensuring sustainable growth and competitiveness in HPC. The study provides valuable insights for policymakers in designing more effective and future-proof HPC strategies.